2021
DOI: 10.1016/j.jval.2021.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Cost-Effectiveness of Malaria Control Interventions: A Systematic Literature Review

Abstract: Objectives: To systematically review the literature on the unit cost and cost-effectiveness of malaria control.Methods: Ten databases and gray literature sources were searched to identify evidence relevant to the period 2005 to 2018. Studies with primary financial or economic cost data from malaria endemic countries that took a provider, provider and household, or societal perspective were included.Results: We identified 103 costing studies. The majority of studies focused on individual rather than combined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 106 publications
1
31
0
Order By: Relevance
“…A systematic review published in 2011 found that the median incremental cost-effectiveness ratio per DALY averted ranged from 8.15 to 150.00 USD (~ 10.00 to 200.00 USD in 2020 value) for intermittent preventive treatment in pregnancy, ITNs, and IRS [ 7 ]. A similar review published in 2021 found a similar range in literature from 2005 to 2018 [ 8 ]. These systematic reviews generally covered studies where the comparator was no intervention; thus the ICER in the studies reviewed would be expected to be lower than when adding the intervention on to the other standard interventions, as was the case in this study since the ICER estimated in this study is effectively marginal rather than generalized.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A systematic review published in 2011 found that the median incremental cost-effectiveness ratio per DALY averted ranged from 8.15 to 150.00 USD (~ 10.00 to 200.00 USD in 2020 value) for intermittent preventive treatment in pregnancy, ITNs, and IRS [ 7 ]. A similar review published in 2021 found a similar range in literature from 2005 to 2018 [ 8 ]. These systematic reviews generally covered studies where the comparator was no intervention; thus the ICER in the studies reviewed would be expected to be lower than when adding the intervention on to the other standard interventions, as was the case in this study since the ICER estimated in this study is effectively marginal rather than generalized.…”
Section: Discussionmentioning
confidence: 59%
“…However, the review identified no cost or cost-effectiveness studies published after the year 2001, and thus did not include the more recent expansion of IRS geographies and products in sub-Saharan Africa. A more recent systematic review covering literature from 2005 to 2018 found no new cost-effectiveness studies of IRS published in this period [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis also suggests PDMC will be highly cost-effective across a wide range of settings, given that the cost of inpatient malaria care in sub-Saharan Africa is $15.64-$137.87. 29 However, cost-effectiveness will depend on the local costs of clinical management and the organisation of health care services.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of public or private provider, the averted cost reflects the total averted healthcare expenditure on treating malaria including out-of-pocket spending. The treatment cost measures were specified as the median provider economic cost of treating an episode of malaria from the systematic review by Conteh, et al , 23 which reported the treatment cost of an uncomplicated episode as US$9.31 and that of a severe episode as US$89.93 in 2018. From 2023 to 2027, the averted treatment cost ( ) due to iMDA for country at year given a proportion of severe episodes ( ) was…”
Section: Methodsmentioning
confidence: 99%